POTENSI REDUKSI LIMPASAN PERMUKAAN DENGAN METODE SOIL CONSERVATION SERVICE - CURVE NUMBER DI KELURAHAN RAWA BUNTU - Steffany Trifena; Dwi Prabowo (Program Studi Perencanaan Wilayah dan Kota, Fakultas Teknik, Universitas Semarang, 2020)
Development in Rawa Buntu Subdistrict caused land use change and made green space area in Rawa Buntu Subdistrict decreased, so it could cause flood. This research was conducted to know the potential of rainwater runoff reduction in each type of land cover in Rawa Buntu Subdistrict to serve as the basis for better planning in the future. The Soil Conservation Service - Curve Number (SCS-CN) method is used to calculate the total rainfall runoff that can be reduced and to know the role of green space in reducing rainwater runoff. The result of the research shows that residential area dominates Rawa Buntu Subdistrict about 65% and green space is only about 18%. The volume of rainfall runoff that can be reduced each month on AMC I, AMC II and AMC III is 74,4MGal, 37,8MGal and 17,9MGal with green space contribution of 27%, 31,2% and 36,4% of the total rainfall runoff that can be reduced for each AMC condition.